Analysis of the Risk Factors Affecting the Size of Fatal Accidents Involving Trucks Based on the Structural Equation Model. Issue 8 (August 2019) - Yuan, Yalong; Yang, Min; Gan, Zuoxian; Wu, Jingxian; Xu, Chengcheng; Lei, Da
For decreasing the casualties and property losses in truck-involved fatal accidents, efforts to identify risk factors and their impacts on the fatal accidents are urgently needed. First, for scaling damage extent in fatal accident, truck occupant injury factor and accident size were selected from occupant- and crash- levels respectively. Then, a general structural model was built to explore the relationships between environmental, roadway, vehicle, driver factors and fatal accident severity. Afterwards, by analyzing 2010 data from the Trucks Involved in Fatal Accidents (TIFA) database, a weighted least squares (WLS) based structural equation model (SEM) was adopted to estimate the parameters of the general structural model. Significant differences between various risk factors determining truck occupant injury factors and accident severity were identified. The results indicate that environmental, roadway, vehicle, and driver factors all have statistically significant effects on the accident size and truck occupant injury factors. However, the extent to which these risk factors impact these two latent endogenous variables differ significantly. Measurement models including different latent risk factors and the corresponding observed variables are then analyzed. The results show that main indicators affecting accident severity are: environmental and roadway factors such as weather, surface conditions; vehicle factors such as truck weight and body type; and driver factors such as age, driving experience, and history of crashes or convictions. Finally, several countermeasures are suggested for truck manufactures and safety planners with the goal of reducing the number and severity of fatal accidents involving trucks.